PENGARUH MODEL PEMBELAJARAN QUESTION STUDENT HAVE DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD AL HIJRAH KOTA MAKASSAR - Erwin Nurdiansyah (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: The Effect of Question Student Have Learning Model in Improving Mathematics Learning Outcomes of Students in the Grade V of SD Al Hijrah Makassar. The purpose of this study Knowing the picture of learning outcomes in mathematics, studying the description of learning outcomes in mathematics after applying the learning model Student Questions Have learned the effectiveness of the application of learning models Student Questions have been in class V students of SD Al Hijrah Makassar City. The study used a Pre-Experimental Design Design. The technique used was to take a sample using a saturated sample, the sample of this study were all fifth grade students of Al Hijrah Elementary School in Makassar who gathered 31 students. The technique used by the author was saturated sampling, so the sample in this study was all fifth grade students of SD Al Hijrah Elementary Makassar, with total 31 students. Based on the results of descriptive analysis of data, it was found that the average acquisition of students 'cognitive scores before the application of the Question Student Have learning model was 39.87 and 61% of students from 31 students' mastery level of material were in the low category. While the average cognitive value of students after applying the Question Student Have learning model was 75.61 and 68% of students from 31 students mastering the material were in the high category. This showed an increased in the acquisition of the average value of students namely from 39.87 to 75.61. This meant that the Question Student Have learning model had effect very in improving student learning outcomes.